2017
DOI: 10.1038/mi.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of autophagy underlies pathogenesis of inflammatory bowel disease

Abstract: Autophagy contributes to cellular homeostasis in the face of nutrient deprivation and other cellular stresses. Cell type-specific functions for autophagy are critical in maintaining homeostasis at both the tissue level and at the whole-organism level. Recent work has highlighted the ways in which human genetic variants modulate autophagy to alter epithelial and immune responses in inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 144 publications
(135 reference statements)
0
24
0
Order By: Relevance
“…And we will explore the underlying mechanisms of the changing LC3B, p62 with time prolonged in depth in further studies. In addition, activation of autophagy has been identified as cytoprotective in some settings, whereas in other cases, sustained or excessive activation of autophagy has been associated with inflammatory pathologies [ 32 , 33 ]. Recent investigations have shown that the phagocytic uptake of cells dying through autophagy induction in human macrophages evokes a pro-inflammatory response as characterized by the induction and secretion of cytokines such as TNF-α, IL-6, IL-8 and IL-10 [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…And we will explore the underlying mechanisms of the changing LC3B, p62 with time prolonged in depth in further studies. In addition, activation of autophagy has been identified as cytoprotective in some settings, whereas in other cases, sustained or excessive activation of autophagy has been associated with inflammatory pathologies [ 32 , 33 ]. Recent investigations have shown that the phagocytic uptake of cells dying through autophagy induction in human macrophages evokes a pro-inflammatory response as characterized by the induction and secretion of cytokines such as TNF-α, IL-6, IL-8 and IL-10 [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such cross-talk may be particularly important in maintaining intestinal homeostasis, as witnessed in human allele variants in these components that are associated with inflammatory conditions such as Crohn’s disease (Parkes et al, 2007). The reader is referred to one of a number of excellent reviews that exist on this topic (Salem et al, 2015, Lassen and Xavier, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Macroautophagy is distinguished from the two other primary types of autophagy in mammalian cells, microautophagy and chaperone-mediated autophagy, by the formation of a double membrane bound phagophore and autophagosome ( 83 ). In its most basic form, autophagy represents a cellular adaptation to starvation and allows the non-specific breakdown of a cell’s own constituents to recycle nutrients and balance biosynthetic pathways ( 84 , 85 ). This form of autophagy, known as non-selective autophagy, is also induced by cellular stress.…”
Section: Innate Immune Modulation Of Autophagymentioning
confidence: 99%